1995
DOI: 10.1128/iai.63.2.741-743.1995
|View full text |Cite
|
Sign up to set email alerts
|

Drug-resistant strains of Mycobacterium tuberculosis exhibit a range of virulence for mice

Abstract: A panel of clinical isolates of Mycobacterium tuberculosis, several of which were resistant to one or more antimycobacterial drugs, were tested for their capacity to give rise to active disease following aerogenic infection of normal immunocompetent mice. The panel exhibited a range of virulence in this model, which followed no clear trend in terms of geographical source, degree of drug resistance, or rate of growth in vitro. Several isolates grew very quickly over the first 20 days in mouse lungs before being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(36 citation statements)
references
References 11 publications
3
33
0
Order By: Relevance
“…Laboratory-adapted strains were isolated .60 years ago and have been passaged many times since. Thus, they do not seem to possess the virulence of the newly emerging clinical strains, such as the highly prevalent Beijing strains [9][10][11]. As we have previously shown [12,13], some of these latter strains are potent inducers of CD4 + Foxp3 + T regs , the numbers of which increase in the lungs of infected mice over time.…”
Section: Introductionmentioning
confidence: 91%
“…Laboratory-adapted strains were isolated .60 years ago and have been passaged many times since. Thus, they do not seem to possess the virulence of the newly emerging clinical strains, such as the highly prevalent Beijing strains [9][10][11]. As we have previously shown [12,13], some of these latter strains are potent inducers of CD4 + Foxp3 + T regs , the numbers of which increase in the lungs of infected mice over time.…”
Section: Introductionmentioning
confidence: 91%
“…174 anti-TB agents, found that drug-resistant strains had a range of virulence. 239 No simple relationship was identified between degree of drug resistance and relative virulence, as defined by growth in lungs following aerogenic exposure to a low dose inoculum. Although these data are important, the exact molecular basis of drug resistance in these organisms was not defined.…”
Section: Virulence and Drug Resistancementioning
confidence: 99%
“…The testing of novel drug compounds (Kelly, Furney, Jessen, & Orme, 1996;), immunotherapy, or vaccines (Abou-Zeid et al, 1996Huygen et al, 1996;Orme, 1988Orme, , 1995Roberts et al, 1995; in the treatment of tuberculosis can also be determined in the mouse model in an effective and economical manner. Virulence studies of the newly emerging multi-drug resistant and totally drug resistant strains of M. tuberculosis have been accomplished using aerogenic challenge, although extreme care must of course be undertaken due to biosafety considerations (Ordway, Sonnenberg, Donahue, Belisle, & Orme, 1995). The guinea pig model is well suited to studies of mycobacterial infections due to the exquisite susceptibility of this animal to M. tuberculosis.…”
Section: Of 52mentioning
confidence: 99%